2023
DOI: 10.1037/trm0000382
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-informed supervision of trainees: Practices of supervisors trained in both trauma and clinical supervision.

Abstract: It is increasingly evident that all clinicians, including trainees, will encounter trauma-exposed clients (Henning et al., 2021). Unfortunately, the practice of trauma-informed supervision (TIS) essential to supporting their work is not yet well articulated, particularly TIS for trainees, and many supervisors lack training in both trauma and clinical supervision (Henning et al., 2021). Accordingly, we interviewed 9 supervisors who had formal training in trauma work as well as clinical supervision (didactic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Ideally, clinicians work to regulate at the moment (inside or outside of the session) at the first sign they are exceeding their window of tolerance. Borders et al (2023) qualitative study on trauma-informed supervision identified helping counselors maintain their own grounding and emotional regulation as a clinical priority. The first step to regulation is interoception, or awareness of one's internal states and bodily sensations (Connell et al, 2018).…”
Section: Emotional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, clinicians work to regulate at the moment (inside or outside of the session) at the first sign they are exceeding their window of tolerance. Borders et al (2023) qualitative study on trauma-informed supervision identified helping counselors maintain their own grounding and emotional regulation as a clinical priority. The first step to regulation is interoception, or awareness of one's internal states and bodily sensations (Connell et al, 2018).…”
Section: Emotional Regulationmentioning
confidence: 99%
“…Keen awareness of clinicians’ own vulnerabilities and how defensive reactions may impact their clients and their sessions together is a key component of professional self-monitoring. All clinicians, including graduate students, should attend their AV due to the reality that they are likely to be exposed to clients with significant trauma histories in their internship experiences (Borders et al, 2023). Currently, the main treatment recommended for clinicians and graduate students in addressing indirect trauma exposure is self-care.…”
Section: Implications For Treatment and Preventionmentioning
confidence: 99%